An Discourse Analysis Educational Values Of Riau Folk Songs “Soleram” - Ade Risya Fitr; Fajriatun Nurjanah; Rizka Muftiari Aulia; Emeliya Sukma Dara Damanik (Jurnal Dunia Pendidikan, 2024)
The study of language refers to discourse analysis. The researcher made this paper based on my discourse analysis to lyrics of Riau folk song entitled Soleram. It was interesting to analyze this song because the researcher really like the song Soleram of which this song’s as the Riau folk song. The objective of this research was to know the pedagogical values particularly with regard to the morality contained in the lyrics of Riau folk song entitled Soleram. It was a descriptive qualitative text and it used semantic as the base theory which related on moral and educational values. The results of the researcher's analysis using semantics as a theoretical basis related to moral and educational values, the researcher found moral and educational values from the song Soleram: a. The first stanza of the song Soleram means the advice of a mother so that her child can maintain a sense of shame so that customs, honour, sharia, religion and good name are maintained. b. In the second stanza, it means that the child can establish good friendships, behave politely, and be loyal friends. c. It closes with the final verse which contains a message to preserve culture that reflects the identity of the Indonesian nation.